Exploring Carbon Pricing in Developing Countries : A Macroeconomic Analysis in Ethiopia - Telaye, Andualem; Benitez, Pablo; Tamru, Seneshaw; Medhin, Haileselassie; Toman, Michael (World Bank, Washington, DC, 2019)
This study uses a computable general equilibrium model to analyze various policy scenarios for a carbon tax on greenhouse gas emissions from petroleum fuels and kerosene in Ethiopia. The carbon tax starts at $5 per ton of carbon dioxide in 2018 and rises to $30 per ton in 2030. Different scenarios examine the impacts with revenue recycling through a uniform sales tax reduction, reduction of labor income tax, reduction of business income tax, direct transfer back to households, and use by the government to reduce debt. Because petroleum fuels and kerosene are a relatively small part of the Ethiopian economy, the carbon tax has quite small impacts on overall economic activity while having a notable proportionate impact on greenhouse gas emissions from these energy sources, depending on the recycling scenario. The carbon tax can raise significant revenue -- up to $800 million per year by 2030. The impacts on the poor through increased cost of living are not that large, since the share of the poor in total use of petroleum fuels and kerosene is small. In terms of income effects through employment changes, urban households tend to experience more impacts than rural households, but the results also depend on the household skill level and the revenue recycling scenario.